E-commerce adoption in SME retail sector: a conceptual model - Amin, Mohammad Ruhul; Hussin, Husnayati (2014)
In the past decades, studies on e-commerce adoption by small businesses have attracted a significant attention and mainly focused on manufacturing, distribution and service sector. E-commerce technology adoption in SMEs and their online presence has added more advantages for step forward. Studies also have done in SMEs retail sector realigning its significance to the economy. Different studies have used different models and theories for E-commerce adoption. This paper attempts to discuss a conceptual model with several influencing factors called technological, organizational and environmental and sub factors to achieve a better understanding on e-commerce adoption procedure. The proposed model is adapted from Tornatzky and Fleischer 1990, framework and explained effective way of e-commerce adoption. SME retail sector is the main focused issue in this study.